Mentorship on Determining Cost of Goods Sold and Profit-Based Selling Prices in MSMEs: Mentorship Penetapan Harga Pokok Penjualan Dan Harga Jual Berbasis Laba Pada UMKM - Halpiah, Halpiah; Putra, Hery Astika; Rosita, Rosita; Agustina, Helda Nia; Ningsih, Okta Ayu; Qistinnisa, Baiq; Putra, Indrata wangsa (Universitas Lancang Kuning, 2025)
The entrepreneurial partnership service was carried out at UD. Asri, with 5 participants, namely 1 owner, 4 employees, aiming to educate and mentor partners on how to determine HPP and profit-based selling prices that can improve business financial performance, using the Participatory Rural Appraisal method, so that the level of partner involvement is higher, using an approach, education, mentorship, practice, and evaluation using an accounting approach, with the results of partners being able to understand the basics of accounting increasing from 40% to 87%, the ability to determine the cost of goods sold from 0% to 60%, the ability to determine profit-based selling prices from 40% to 80%, while the willingness to continue determining the HPP of profit-based selling prices increased from 20% to 86% in addition to the results of the PKM partners being able to produce products that had been discontinued, namely cassava chips, producing new products in the form of saleh bananas, and differentiating tempeh chips products into three choices of flavors, sizes and prices to attract new consumers, reach a wider market and increase productivity and business profits